Pendampingan Pemahaman Fintech pada UMKM Makanan di Kabupaten Banyumas - Triani Arofah; Wita Ramadhanti; Oman Rusmana (Jurnal Pengabdian Bisnis dan Akuntansi, 2026)
This study describes a mentoring process aimed at building fintech understanding among food micro, small, and medium enterprise (MSME) owners in Banyumas Regency who are registered GrabFood partners but lack merchant-side understanding of OVO payment processing and QRIS verification. Using a descriptive qualitative case study approach, the research team acted as consumers ordering through the GrabFood Self-Pickup feature, paying via OVO, and directly observing how MSME owners handled, verified, and responded to digital payment transactions before and after guided mentoring. This study also incorporates survey data from 34 MSME respondents to characterize the broader profile of fintech understanding among food MSMEs in the region. Findings show that most owners initially adopted a passive "as long as money comes in" attitude toward digital payments, accepting transactions without understanding the underlying process flow, fund settlement schedule, or verification steps. Survey results confirm that while respondents scored well on financial digitalization dimensions (mean 4.08) and GrabFood/OVO usage perception (mean 3.87), business performance scores were comparatively lower (mean 3.23), suggesting a gap between platform adoption and operational outcomes. Following repeated, transaction-based mentoring, owners demonstrated improved ability to independently process GrabFood orders, identify payment methods, and verify QRIS transactions. The study illustrates that fintech literacy among digitally underserved MSME owners can be cultivated through simple, contextual mentoring grounded in real, everyday transactions.